Optimization Of Friction Properties Of Kenaf Polymer Composite As An Alternative Friction Material - Mustafa, Ashafi'e; Abdollah, Mohd Fadzli; Amiruddin, Hilmi; Shuhimi, Fairuz Fazillah; Muhammad, Noryani (Emerald Group Publishing Limited, 2017)
Purpose – The aim of this study is to determine the optimal parameters for friction coefficient of kenaf/epoxy (KE) composite as an alternative friction material. Design/methodology/approach – The design of experiment was constructed using the Taguchi method. KE specimens were formed into 10 mm diameter pins using hot compression technique with different types, weight concentrations and treatments of kenaf. The samples were tested using a pin-on-disc tribometer at different applied loads, speeds and operating temperatures with a constant sliding distance of 3 km under dry sliding conditions. Findings – The sample with 45 wt.% of non-treated kenaf fibre, tested at 19.62 N, 500 rpm and 100°C was found to be the optimized combination to obtain higher friction. From the confirmation test, the experimental friction coefficient is acceptable because of fall within 95 per cent confidence interval. Predominant wear mechanisms are identified as micro-crack and debonding of fibre. Originality/value – KE composite can be considered as an alternative friction material, as the tested friction coefficient is within the suggested range for the friction material applications.